2020
DOI: 10.7554/elife.58954
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental determinants of variation in the plasma lipidome of older Australian twins

Abstract: The critical role of blood lipids in a broad range of health and disease states is well recognised but less explored is the interplay of genetics and environment within the broader blood lipidome. We examined heritability of the plasma lipidome among healthy older-aged twins (75 monozygotic/55 dizygotic pairs) enrolled in the Older Australian Twins Study (OATS) and explored corresponding gene expression and DNA methylation associations. 27/209 lipids (13.3%) detected by liquid chromatography-coupled mass spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
2
8
0
Order By: Relevance
“…In this same sample of twins, it was shown that 20% of the urinary NMR metabolomic profile was stable over a 2-month period and that both common genetic and shared environmental factors contribute to the short-term stability of the urinary metabolome in adults [49]. Previous studies investigating the blood metabolome in adult populations [8,[10][11][12][13], also obtained very limited evidence for contributions of the common environment, while the influence of genetics is substantial. To date, genome-wide association studies for blood metabolites have identified more than 800 metabolite loci, with an average heritability of metabolite loci of 6% for lipids and lipid-like molecules and of 1% for organic acids and derivatives [18].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this same sample of twins, it was shown that 20% of the urinary NMR metabolomic profile was stable over a 2-month period and that both common genetic and shared environmental factors contribute to the short-term stability of the urinary metabolome in adults [49]. Previous studies investigating the blood metabolome in adult populations [8,[10][11][12][13], also obtained very limited evidence for contributions of the common environment, while the influence of genetics is substantial. To date, genome-wide association studies for blood metabolites have identified more than 800 metabolite loci, with an average heritability of metabolite loci of 6% for lipids and lipid-like molecules and of 1% for organic acids and derivatives [18].…”
Section: Discussionmentioning
confidence: 85%
“…Previous heritability studies of metabolomics data in various biofluids found that about 50% of the variance in metabolite levels is due to additive genetic factors [6,7]. Non-additive (i.e., dominant genetic effects) and common (shared) environmental factors (i.e., shared by family members) generally have a minor influence on metabolite levels [8][9][10][11][12][13]. Some nuance on the contribution of genetic factors is possible: the contribution to individual differences in metabolite levels differs per metabolite class and subclass, with generally somewhat higher heritability estimates observed for lipids and lipid-like molecules than for organic acids and derivatives [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A median estimate of heritability, the variation in ceramide levels to due genetic factors, was reported at 45% for all ceramides, using family-based variance-components analyses. Other estimates of narrow-sense heritability have estimated the heritability of circulating ceramides to be between 9% and 62% [93,[97][98][99]. For example, if a DNA variant affects the levels of a ceramide species in circulation, then the differences in that ceramide species will be lifelong differences, as genotype is allocated at conception.…”
Section: Current Genetic Studies Of Ceramidesmentioning
confidence: 99%
“…In this same sample of twins, it was shown that 20% of the urinary NMR metabolomic profile was stable over a 2-month period and that both common genetic and shared environmental factors contribute to the short-term stability of the urinary metabolome in adults [52]. Previous studies investigating the blood metabolome in adult populations [8,[10][11][12][13]] also obtained very limited evidence for contributions of the common environment, whereas the influence of genetics is substantial. To date, genome-wide association studies for blood metabolites have identified more than 800 metabolite loci, with an average heritability of metabolite loci of 6% for lipids and lipid-like molecules and of 1% for organic acids and derivatives [18].…”
Section: Discussionmentioning
confidence: 87%
“…Previous heritability studies of metabolomics data in various biofluids found that about 50% of the variance in metabolite levels is due to additive genetic factors [6,7]. Nonadditive (i.e., dominant genetic effects) and common (shared) environmental factors (i.e., shared by family members) generally have a minor influence on metabolite levels [8][9][10][11][12][13]. Some nuance on the contribution of genetic factors is possible: the contribution to individual differences in metabolite levels differs per metabolite class and subclass, with generally somewhat higher heritability estimates observed for lipids and lipid-like molecules than for organic acids and derivatives [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%